ASPEK-ASPEK PENDIDIKAN PENGATURAN DIRI DALAM TEKS ŚIVASUTRA - I Putu Suweka Oka Sugiharta (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Self-regulation is a very important part of the whole educational process. This section covers basic education to the most complex. The Śivasutra Text describes aspects of self-regulation education starting from the most basic to the complex level. The basic and simple aspects are related to the habits and processes of human learning in everyday life with worldly nuances. This indicates that the process of religious learning in Hinduism is not too hasty to direct students towards the transcendent dimension. If the learning process has started from simple things then a learner will be able to become a complete human being. Apart from being competent in carrying out their obligations as members of society, they will also be ready to understand more transcendental dimensions. The purpose of this study is to get an overview of the self-regulatory aspects in the Śivasutra text. The method used in this study is a qualitative method because it involves description, analysis, and interpretation of words. The results of this research are that in the Śivasutra texts there are aspects of self-regulation education such as the Sivais-Tantrik style, basic learning, daily learning, wise use of knowledge, wisdom to see the material world, and the peak is awareness of one's True Self.